RECONSTRUCTING THE IDEA OF PRAYER SPACE: A CRITICAL ANALYSIS OF THE TEMPORARY PRAYING PLATFORM PROJECT OF 2ND YEAR ARCHITECTURE STUDENTS IN THE NATIONAL UNIVERSITY OF MALAYSIA (UKM) - Utaberta, Nangkula; Bahar, Mohammad Arsyad (Journal of Islamic Architecture, 2013)
AbstractGod created human as caliph on this earth. Caliph means leader, care-taker and guardian. Therefore humans have an obligation to maintain, preserve and conserve this natural for future generations. Today we see a lot of damage that occurs in the earth caused by human behavior. Islam saw the whole of nature as a place of prayer that must be maintained its cleanliness and purity. Therefore as Muslims we need to preserve nature as we keep our place of prayer. The main objective of this paper is to re-questioning and re-interpreting the idea of sustainability in Islamic Architecture through a critical analysis of first project of 2nd year architecture student of UKM which is the â€œTemporary Praying Platformâ€. The discussion itself will be divided into three (3) main parts. The first part will be discussing contemporary issues in Islamic Architecture especially in the design of Mosques while the second part will expand the framework of sustainability in Islamic Architecture. The last part will be analyzing some sample of design submission by 2nd year students of UKM on the temporary praying platform project. It is expected that this paper can start a further discussion on the inner meaning in Islam and how it was implemented in the design of praying spaces in the future.Keywords: Â Sustainability, Islamic Architecture, Temporary Praying PlatformAbstrakTuhan menciptakan manusia sebagai khalifah di muka bumi ini. Khalifah berarti pemimpin, penjaga dan wali. Oleh karena itu, manusia memiliki kewajiban untuk memelihara, menjaga dan melestarikan alam ini untuk generasi mendatang. Sekaranginikitatelahmelihat banyak kerusakan yang terjadi di bumi yang disebabkan oleh perilaku manusia itu sendiri yang disebutkan sebagai khalifah di bumi. Islam melihat seluruh alam sebagai tempat beribadah yang harus dijaga kebersihan dan kemurniannya, oleh karena itu, sebagai umat Islam adalah perlu melestarikan alam seperti menjaga tempat ibadah mereka. Tujuan utama dari makalah ini adalah untuk mempertanyakan dan menafsirkan kembali gagasan keberlanjutan (sustainable) dalam Arsitektur Islam melalui analisis kritis tugasÂ  pertama dari mahasiswa arsitektur angkatan Â tahun Â kedua dari Universiti Kebangsaan Malaysia (UKM), yaitu tugas perancangan " tempat beribadah sementara "atau â€œtemporary praying platformâ€ . Kajiandibagi menjadi tiga bagian utama. Bagian pertama akan membahas isu-isu kontemporer dalam Arsitektur Islam terutama dalam desain masjid. Kajian kedua adalah kerangka keberlanjutan dalam arsitektur Islam. Bagian ketiga adalah analisis dari beberapa sampel pengajuan desain oleh mahasiswa. Diharapkan tulisan ini dapat memulai diskusi lebih lanjut tentang makna batin dalam Islam dan bagaimana penerapannya dalam desain ruang beribadah yang sustainable.Kata kunci:Keberlanjutan, Arsitektur Islam, tempat beribadah sementaraÂ